Assessing the factors influencing continued use of online-food-delivery services and the impact on health: a multi-group analysis. (1st June 2023) - Ray, Arghya; Bala, Pradip Kumar; Jain, Rashmi
Online-food-delivery (OFD) services among consumers have not only revolutionised the food industry but have also impacted the lifestyle of individuals. The purpose of this study is to empirically explore the factors that affect the use of OFDs, and the influence of continued use of OFDs on consumer's food consumption pattern and health concerns. A mixed-method approach was considered, comprising of qualitative interviews of 12 OFD users and later a quantitative cross-sectional survey of 292 Gen Y OFD users from India. The findings suggest a significant association between emotional values, conditional values, monetary values and health consciousness on intention. Additionally, there is also a notable positive influence of continuance intention on changing-food-consumption-pattern and health issues. A multi-group analysis was also conducted to assess the varying impact of the variables when compared among different groups (place-of-stay, gender, and occupation). This study concludes with the research implications, limitations and future scope.